The Diversity of Undergrowth Species in The Eastern Part of Gunung Papandayan, Garut, West Java KEANEKARAGAMAN JENIS TUMBUHAN BAWAH DI GUNUNG PAPANDAYAN BAGIAN TIMUR, GARUT, JAWA BARAT - Iwan Hilwan; Idealisa Masyrafina (Jurnal Silvikultur Tropika, 2015)
Gunung Papandayan has the potential of various types of fauna and flora that has become the unity in its natural environment. The objectives of this research was to determine the composition, diversity and potential of undergrowth that are found in the eastern part of Gunung Papandayan. The total of undergrowth species on Gunung Papandayan approximately 101 species of 34 families. The level of undergrowth diversity on five sites vary with a value of highest H’ at Supabeureum (3.36), while Tegal Mariuk has the smallest value of H’ (2.40). The low level of vegetation dominance indicated that undergrowth in five sites spreadon a lot of species. Undergrowth vegetation communities in five sites are differs with IS score was < 75 %. Undergrowth species which are found on Gunung Papandayan has potential as food, medicinal plants, ornamental plants, and livestock feed.Keywords: analysis of vegetation, diversity, Gunung Papandayan, undergrowth